MOA-2022-BLG-033Lb, KMT-2023-BLG-0119Lb, and KMT-2023-BLG-1896Lb: Three low mass-ratio microlensing planets detected through dip signals - Han, Cheongho; Bond, Ian A.; Jung, Youn Kil; Albrow, Michael D.; Chung, Sun-Ju; Gould, Andrew; Hwang, Kyu-Ha; Lee, Chung-Uk; Ryu, Yoon-Hyun; Shvartzvald, Yossi; Shin, In-Gu; Yee, Jennifer C.; et al. (Astronomy and astrophysics (Berlin), 2025)
Aims . We examined the anomalies in the light curves of the lensing events MOA-2022-BLG-033, KMT-2023-BLG-0119, and KMT- 2023-BLG-1896. These anomalies share similar traits: they occur near the peak of moderately to highly magnified events and display a distinct short-term dip feature. Methods . We conducted detailed modeling of the light curves to uncover the nature of the anomalies. This modeling revealed that all signals originated from planetary companions to the primary lens. The planet-to-host mass ratios are very low: q ~ 7.5 × 10 −5 for MOA-2022-BLG-033, q ~ 3.6 × 10 −4 for KMT-2023-BLG-0119, and q ~ 6.9 × 10 −5 for KMT-2023-BLG-1896. The anomalies occurred as the source passed through the negative deviation region behind the central caustic along the planet-host axis. The solutions are subject to a common inner-outer degeneracy, which results in varying estimations of the projected planet-host separation. For KMT-2023-BLG-1896, although the planetary scenario provides the best explanation for the anomaly, the binary companion scenario is possible. Results . We estimated the physical parameters of the planetary systems through Bayesian analyses based on the lensing observables. While the event timescale was measured for all events, the angular Einstein radius was not measured for any. Additionally, the microlens parallax was measured for MOA-2022-BLG-033. The analysis identifies MOA-2022-BLG-033L as a planetary system with an ice giant with a mass of approximately 12 times that of Earth orbiting an early M dwarf star. The companion of KMT-2023-BLG-1896L is also an ice giant, with a mass of around 16 Earth masses, orbiting a mid-K-type main-sequence star. The companion of KMT-2023-BLG- 0119L, which has a mass around that of Saturn, orbits a mid-K-type dwarf star. The lens for MOA-2022-BLG-033 is highly likely to be located in the disk, whereas for the other events the probabilities of the lens being in the disk or the bulge are roughly equal.